The surgery in the diagnosis of Hodgkin’s disease - Mate, Miguel; Martínez de Lima, Gladys; Lima, Fabio; Priario, Julio C (Cirugía del Uruguay, 1975)
Out of 150 cases of Hodgkin's disease treated in fhe Hospital de Clínicas from 1967 to 1973, 72 were submitted to diagnostic laparotomy. Thirty five of them ( 48.6 % ) underwent modifications of their clinical staging as a consequence of surgical findings, Twenty four (33 % ) pathologic spleens were found; 12 of them corresponded to patients in whom enlargement of the spleen was not evident. In 18 cases (25 % ) lymph nade involvement, which had not been clinically suspected, was found. Systematic laparotomy results then in a better knowledge of the disease and in therapeutic plans more adjusted to its actual extension. On the. other hand, splenectomy means a reduce of the potential risks of a radiotherapy on the kidney and left pulmonary base. In the present series there was a morbility of 11 % and a mortality of 1.3 % .